Determination of thermal conductivity of sands under varying moisture, drainage/wetting, and porosity conditions - applications in near-surface soil moisture distribution analysis - Smits, Kathleen M., author; Sakaki, Toshihiro, author; Limsuwat, Anuchit, author; Illangasekare, Tissa H., author; Colorado State University, publisher (Colorado State University. Libraries, 2009)
A class of problems in hydrology and remote sensing requires improved understanding of how water and heat flux boundary conditions affect the soil moisture processes in the shallow subsurface near the land/atmospheric interface. In these systems, a clear understanding of how variations in water content, soil drainage/wetting and porosity conditions affect the soil's thermal behavior is needed for the accurate detection of buried objects such as landmines, however, very few experimental data showing the effects of these variations are available. In this study, the effect of soil moisture, soil hysteretic behavior and porosity on the thermal conductivity of some sandy soils was investigated. For this experimental investigation, a Tempe cell was modified to have a network of sampling ports, continuously monitoring water saturation, capillary pressure, temperature, and soil thermal properties. The water table was established at mid elevation of the cell and then lowered slowly. The initially saturated soil sample was subjected to slow drainage, wetting, and secondary drainage cycles. After liquid water drainage ceased, evaporation was induced at the surface to remove soil moisture from the sample to obtain thermal conductivity data below the residual saturation. For the test soils studied, thermal conductivity increased with increasing soil density and moisture content while thermal conductivity values were similar for soil drying/wetting behavior. Thermal properties measured in this study were then compared with independent estimates made using empirical models from literature. These soils will be used in a proposed set of experiments in intermediate scale test tanks to obtain data to validate methods and modeling tools used for landmine detection.
Hydrology days 2009
AGU hydrology days 2009
2009 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2009.